Patch test results in children and adolescents suffering from allergic contact dermatitis – comparison of patients with and without atopic dermatitis - Bacharewicz-Szczerbicka, Joanna; Reduta, Teresa; Pawłoś, Anna; Flisiak, Iwona (Dermatology Review/Przegląd Dermatologiczny, 2017)
Introduction . Allergic contact dermatitis is a more and more frequently diagnosed skin disease in children and adolescents. It may coexist with atopic dermatitis. The frequency of allergy to certain contact haptens is determined by numerous factors. Objective. To assess the frequency of allergy to selected contact allergens among children and adolescents with symptoms of contact eczema. Material and methods . Two hundred seventy-three consecutive patients aged 4–18 years treated because of allergic contact eczema were included in this study. The demographic data and patch test results were assessed in the total group and separately in two age groups of patients without and with atopic dermatitis. Results . The total group examined included 71 (44 female and 27 male) children and 202 (145 female and 57 male) adolescents. Atopic dermatitis was diagnosed in 64 patients. The patch test results were positive in 36.3% of examined subjects: 26.5% of children and 39.6% of adolescents, with a similar frequency in patients with and without atopic dermatitis. The most common contact sensitizers were nickel sulfate (20.1%), cobalt chloride (12.8%), p-phenylenediamine (3.3%), potassium dichromate and fragrances (2.9% each), balsam of Peru and neomycin sulfate (1.5% each). Cobalt, chromate, fragrances and balsam of Peru more frequently sensitized patients with atopic dermatitis. Among the younger boys with atopic dermatitis there were no cases of contact allergy to nickel and cobalt, while in the atopic adolescent males the results with each of these allergens were positive in 20% of those examined. Conclusions . Contact allergy is detected similarly frequent in children and adolescents with and without atopic dermatitis. The very high prevalence of allergy to nickel and cobalt is a significant problem among teenage girls and boys with atopic dermatitis.